Pengaruh Pertumbuhan Ekonomi Terhadap Kemiskinan Di Kabupaten Kepulauan Selayar - Nur Aksih Islamiah; Arniati, Arniati; Ismail Rasulong (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The purpose of the researcher in writing this thesis is to determine the effect of economic growth on poverty in Selayar Islands Regency. The method used in this study is a quantitative approach with simple regression analysis, using secondary data from 2014-2023. The results of the study indicate that although there has been economic growth in Selayar Islands Regency in recent years, this growth has not had a significant effect on poverty levels. This can be caused by the uneven distribution of the benefits of economic growth, where economic growth is only enjoyed by a small part of society, especially high-income groups, while most people, especially those in the lower classes, do not feel the benefits.